THE ROLE OF LITHOGEN AND HYDROCLIMATIC ENVIRONMENT OF MIRZACHUL IN THE FORMATION OF AGROLANDSCAPES UNDER CLIMATE CHANGE (Scientific journal of the Fergana State University, 2026)
The article comprehensively covers the role of the lithogenetic and hydroclimatic environment of the Mirzachul district in the formation of agricultural landscapes in the context of climate change, the influence of its geological and geomorphological structure on the movement of groundwater and surface water. The influence of climate indicators on natural conditions and components, negative consequences of climate change, problems and solutions, public health issues.